Medical Informatics: Once More Towards Systematization - Haux, R. (Methods of Information in Medicine, 1996)
Commenting on a paper by Van Bemmel (Medical Informatics, Art or Science? [1]), the following questions are raised: What is the meaning of medical informatics?, How to systematize medical informatics?, Is medical informatics an art, a science or a technology?. It is argued that medical informatics is concerned with the systematic processing of data, information and knowledge in medicine and health care, and that medical informatics is not just the application of computers in these fields. Three classifications for medical informatics research and education are presented. It is concluded that medical informatics is a scientific medical discipline, similar to surgery, internal medicine, epidemiology, or microbiology; and that medical informatics has a strong relationship with the health sciences concerning its field of application, and to informatics concerning its methods and tools. It is a cross-sectional discipline, with relevance for virtually all other specialties of medicine and the health sciences. This is the reason for its impact on research and education in these specialties. It also causes that the quality of the processing of data, information and knowledge has a direct and considerable effect upon the quality of health care in practically all these specialties.
Keywords: Medical Informatics; Health Informatics; Medicine; Health Care